ENUMERASI TOTAL POPULASI MIKROBA TANAH GAMBUT DI TELUK MERANTI KABUPATEN RIAU - Rahmi Fitria; Delita Zul; Bernadeta Leni F (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
Teluk Meranti is one of the peatland area in Riau province. Most of these lands have beenchanged into palm oil plantation, timber plantation, agricultural area and settlement. Theaim of this research was to analyze the impact of land use changes on soil physical-chemical characteristics and microbial cell number. Soil samples were taken from eightdifferent locations, namely primary forest as control, secondary forest, rubber plantation(15 monthsyears old), rubber forest (40-60 years old), palm oil plantation (7-8 years old),acacia plantation (2-3 years old), corn field, and cassava field. Microbial cell number wasdetermined by spread plate method, employing appropriate media for the growth ofbacteria, fungi and actinomycetes. The results showed that the soil humidity, soiltemperature, percentage of soil dry weight, water content, soil bulk density and pH rangedfrom 29,63-55,88%, 27-31,5 o C, 14,9-35,5%, 64,9-85,1%, 0,16-0,39 g/cm 3 and 3,63-4,00,respectively. The copiotrophic bacterial cell number ranged from 0,6x10 5 -1,8x10 5 CFU/gsoil where the highest population was at the palm oil plantation,whereas the oligotrophicbacterial cell number ranged from 0,5x10 5 -1,4x10 5 CFU/g soil where the highest populationwas at the palm oil plantation. The population of fungi ranged from 0,4x10 5 -1,0x10 5 CFU/gsoil where the highest population was at the corn field. The population of actinomycetesranged from 0,4x10 5 -10,7x10 5 CFU/g soil where the highest population was at the palm oilplantation. Land use changes caused microbial cell number increased. The results indicatedthat land use changes influenced the microbial cell numbers.